Kajian Pemilihan Sistem Drainase Berkelanjutan dalam Penanggulangan Banjir Perkotaan di Kec. Medan Selayang, Kota Medan - Ikhwan, Fikri Auza’i (Universitas Harapan Medan, 2024)
Medan Selayang sub-district is one of the sub-districts in Medan City that experiences urban flooding problems. There are at least seven flood points found in the area. Until now, the solution has been to increase the size of the existing drainage channels, which is still a conventional drainage system that adheres to the concept of grey infrastructure. Therefore, it is necessary to find a new method of solving urban flooding problems that is more sustainable, where rainwater can flow and not cause flooding, but also has the opportunity to be absorbed into the soil layer to increase groundwater reserves. Sustainable drainage systems are one method that can solve these problems. There are at least ten methods in sustainable drainage system, therefore a decision-making analysis is needed to select the most appropriate infrastructure to be implemented in Medan Selayang Sub-district. Decision-making is done with the Simple Additive Weighting (SAW) method and the following order is obtained: First place with a score of 130 is occupied by rainwater harvesting, followed by permeable pavement and rain garden with a final score of 128 each.